Analysis of mobility changes caused by COVID-19 in a context of moderate restrictions using data collected by mobile devices - Paiva, Sara (2022)
Since its inception, COVID-19 has changed several dynamics in society, both on a personal and professional level. Mobility was one of the most affected aspects, as a result of the necessary social distancing and preventive measures that had to be enacted by the various countries and which restricted, at various times, freedom of movement. The impact that COVID-19 had, and still has, on mobility is important to be understood so that the necessary measures can be taken in order to return to normality and, for example, not regress in the steps that were being taken in encouraging the use of public transport as a measure to combat the carbon footprint as well as traffic congestion in cities. This paper intends to analyze the reality of Spain and Portugal, in the period between May 10th and July 2nd, 2021, in which both countries had already finished restricting mobility measures. The study used data from Google Community Mobility Reports and was done by regions, taking into account the average age of inhabitants and the number of inhabitants in each region. The analysis focused on different categories of places such as retail and recreation, groceries and pharmacies, parks, transit stations, workplaces, and residential. One of the main conclusions of this study is the lower use of public transports for fear of a greater risk of infection. This could be a problem in the medium term if this trend continues. On the other hand, it is important to highlight a greater presence in parks after the end of the lockdown, which promotes healthy habits that combat problems such as overweight or obesity. COVID-19 can be seen as an opportunity to promote more active mobility through the creation of infrastructure, such as for bicycles.